Gut microbiota in human health: insights and discussion on the role of probiotics - Patwari, Sudhanshu (International Journal of Scientific Reports, 2022)
Gut microbiota remains stable and individualized throughout life, but there are inter-species or intra-species variations that may be controlled by various environmental factors. Several diseases may be associated with dysbiosis like inflammatory bowel disease (IBD), obesity, diabetes mellitus, irritable bowel syndrome (IBS), gastric and colon cancer, and sometimes colorectal polyps, non-alcoholic steatohepatitis (NASH), and liver cirrhosis, because of the gut-derived neurotoxins. There is a 10% to 30% risk of development of post-infectious IBS despite the beneficial effects of a low FODMAP diet on IBS symptoms. This diet reduces the luminal concentration of one of the most common bacteria that is the Bifidobacterium. Therefore, probiotics help in the restoration of normal gut microbiota, are a valuable tool in the treatment of certain diseases and help in recovering microbial balance in the gut. Bifidobacterium W11 is a novel probiotic with certain special characteristics that can be of benefit in dysbiosis. This review evaluates gut microbiota dysbiosis, associated complications of dysbiosis, and benefits of treatment with probiotics based on focused group discussions of various experts from India, followed by guidance statements based on analysis of published literature. The beneficial effects of Bifidobacterium longum W11 (B. longum W11) in the management of IBS, IBD, and liver diseases have been elaborated. The proposed management strategy can effectively aid the management of gut dysbiosis in several gastrointestinal conditions and help in understanding the judicious use of probiotics.